Analisis Hukum terhadap Pemalsuan Data Otentik di Persidangan: Perspektif Hukum Positif dan Hukum Pidana Islam - Lase, Sri Wulandari; Ramadani, Ramadani (IAIN Langsa, 2025)
This study aims to analyze the falsification of authentic data in court proceedings from the perspectives of positive law and Islamic criminal law, focusing on the conformity of legal norms and the sanctions applied. This article falls under library research with a qualitative approach. The methodology used includes normative legal studies and comparative studies. The findings reveal that, in Indonesian positive law, the falsification of authentic data is regulated under the Criminal Code (KUHP) with strict criminal sanctions, while in Islamic criminal law, such actions are categorized as crimes that undermine the principles of justice, with ta'zir sanctions adjusted to the severity of the violation. This study emphasizes the importance of enforcing fair laws to maintain the integrity of the judicial system.